PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Zuraida, Ida (Universitas Muhammadiyah Palembang, 2019)
The purposes of the study was to determine the effect of capital structure , firm size, profitability and dividen policy on the company value. This serearch was in automotive companies listed on the indonesia stock exchange in 2012-2016. The data used secondary data with annual financial statement. Quantitative and qualitative data analysis methods used SPSS as measuring tool. Data analysis techniques used simultaneous tests and partial tests on the annual financial statements of automotive companies listed on the Indonesia stock exchange. The result of the study partially addressed the capital structure variables and firm size had a significant positive effect on the value of the company and profitability variables and dividend policy did not effect the value of the company while simultaneous testing of capital structure variable ,firm size , profitability and dividend policy had a significant effect on company value.